2009
DOI: 10.1152/ajpendo.90769.2008
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cortisol production rates, free cortisol, and 11β-HSD-1 expression correlate with visceral fat and insulin resistance in men: effect of weight loss

Abstract: Purnell JQ, Kahn SE, Samuels MH, Brandon D, Loriaux DL, Brunzell JD. Enhanced cortisol production rates, free cortisol, and 11␤-HSD-1 expression correlate with visceral fat and insulin resistance in men: effect of weight loss. Am J Physiol Endocrinol Metab 296: E351-E357, 2009. First published December 2, 2008; doi:10.1152/ajpendo.90769.2008.-Controversy exists as to whether endogenous cortisol production is associated with visceral obesity and insulin resistance in humans. We therefore quantified cortisol pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 49 publications
4
70
0
5
Order By: Relevance
“…These findings support a shorter-term study that showed no differences in salivary cortisol levels following 18 days on a moderately energy-restricted diet of 1000 kcal/day [54]. Also, 3 months on a moderately energy-restricted diet of 1000 kcal/day, followed by a period where participants were transitioned back to solidfoods over 2 weeks and then spent 3 months on a weight maintenance diet, had no effect on cortisol production rate, either absolute values or normalized to fat free mass [55]. However, in that study cortisol production rate normalized to fat mass or intra-abdominal fat mass increased by 40% and 100%, respectively, after weight loss [55].…”
Section: Effects Of Energy Restriction On Activity Of the Hpa Axis Inmentioning
confidence: 88%
See 1 more Smart Citation
“…These findings support a shorter-term study that showed no differences in salivary cortisol levels following 18 days on a moderately energy-restricted diet of 1000 kcal/day [54]. Also, 3 months on a moderately energy-restricted diet of 1000 kcal/day, followed by a period where participants were transitioned back to solidfoods over 2 weeks and then spent 3 months on a weight maintenance diet, had no effect on cortisol production rate, either absolute values or normalized to fat free mass [55]. However, in that study cortisol production rate normalized to fat mass or intra-abdominal fat mass increased by 40% and 100%, respectively, after weight loss [55].…”
Section: Effects Of Energy Restriction On Activity Of the Hpa Axis Inmentioning
confidence: 88%
“…Also, 3 months on a moderately energy-restricted diet of 1000 kcal/day, followed by a period where participants were transitioned back to solidfoods over 2 weeks and then spent 3 months on a weight maintenance diet, had no effect on cortisol production rate, either absolute values or normalized to fat free mass [55]. However, in that study cortisol production rate normalized to fat mass or intra-abdominal fat mass increased by 40% and 100%, respectively, after weight loss [55]. While these three studies involving moderate energy restriction showed no clear changes in HPA axis function, another study of a 90-day diet of 800 -1500 kcal/day in obese women showed decreased ACTH and cortisol levels measured during an oral glucose tolerance test [56].…”
Section: Effects Of Energy Restriction On Activity Of the Hpa Axis Inmentioning
confidence: 95%
“…Previous studies suggested that increased serum cortisol level in men is mainly mediated through 11b-hydroxysteroid dehydrogenase type 1 (11b-HSD1) activity [24,25]. 11b-HSD1is a bidirectional enzyme, located in the abdominal fat mass and omental subcutaneous tissue, and mediates the conversion of cortisone to cortisol [26,27] thermore there are gender di erences in 11b-HSD1 activity, which is greater in men [20], and 5a-reductase activity, which is greater in women [28].…”
Section: Discussionmentioning
confidence: 99%
“…In a group of 24 men and 30 women (ages 19 -70 yr, BMI 19 -64 kg/m 2 ), daily cortisol production rates ranged from 6.6 to 39 mol/m 2 based upon isotope-dilution mass spectrometry (55,56 (9,42)]. In contrast, analytically estimated ACTH efficacy (defined by asymptotically maximal ACTH-stimulated pulsatile cortisol secretion) would be 136 and 113 mol/day in men and women, respectively.…”
Section: Discussionmentioning
confidence: 99%